Fighting unemployment : the limits of free market orthodoxy. - Howell, David (Oxford University Press, 2005)
Critically assessing the widely accepted view that the cause of unemployment is excessive labor market regulation and overly generous welfare state benefits, this book's chapters include both cross-country statistical analyses and country case studies.